GENDER AND GENDER-SPECIFIC SPECIFICITY OF QUALITY OF LIFE IN PATIENTS WITH PROSOPLEGIA - Urinov, M.B.; Ramazonova, Sh.Sh.; Qosimova, N.T. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the quality of life of patients with prosoplegia syndrome in relation to both gender and gender lateralization. Materials and Methods: the SF-36 test for quality of life research was used. Patients with peripheral nervous system disease with age-appropriate male and female paralysis were selected for the main group of patients. For the SF-36 test, there was a trend of higher scores on virtually all bands in feminine group men and feminine group women. Results: According to the analysis of scores on individual indicators of SF-36, the quality of life was several times higher in the masculine subgroup in the male group, while higher quality of life was found in the feminine-type group of women. Conclusion: all indicators of quality of life in the female group are lower than in the male group, compared with the lateralization of the pathological process, there are no significant differences in the lateralization of the pathological process in the male group, only a chaotic distribution of indicators without certain patterns